X-ray crystallographic and biochemical characterizations of a mutant photosystem II complex from Thermosynechococcus vulcanus with the psbTc gene inactivated by an insertion mutation - Henmi, Takahiro (International Union of Crystallography, 2008)
The crystal structure of a photosystem II (PSII) dimer from Thermosynechococcus vulcanus with its psbTc gene inactivated by insertion mutation of an antibiotic cassette in a site in the C-terminal region was analyzed at 3.8 Å resolution. In the crystal structure of the mutant PSII, the transmembrane helix of PsbTc remains, whereas the C-terminal loop of PsbTc has disappeared. In addition, the PsbM subunit, which seemed to be lost in a PsbTc-deletion mutant PSII of T. elongatus, is still present. The deletion of the C-terminal loop of PsbTc in the mutant PSII was verified by mass spectrometry. Thus, the insertion mutation of psbTc eliminated only the C-terminal loop of this subunit. Nevertheless, some features of the mutant PSII, namely a destabilization of the dimeric form and a slight decrease of the oxygen-evolving activity, were observed in the mutant, indicating that the C-terminal loop of PsbTc functions to maintain the stability of the PSII dimer and the activity of oxygen evolution.